Digital watermarking and steganography - Cox, I. J. (Ingemar J.) (Amsterdam ; Boston : Morgan Kaufmann Publishers, 2008)
Digital audio, video, images, and documents are flying through cyberspace to their respective owners. Unfortunately, along the way, individuals may choose to intervene and take this content for themselves. Digital watermarking and steganography technology greatly reduces the instances of this by limiting or eliminating the ability of third parties to decipher the content that he has taken. The many techiniques of digital watermarking (embedding a code) and steganography (hiding information) continue to evolve as applications that necessitate them do the same. The authors of this second edition provide an update on the framework for applying these techniques that they provided researchers and professionals in the first well-received edition. Steganography and steganalysis (the art of detecting hidden information) have been added to a robust treatment of digital watermarking, as many in each field research and deal with the other. New material includes watermarking with side information, QIM, and dirty-paper codes. The revision and inclusion of new material by these influential authors has created a must-own book for anyone in this profession. *This new edition now contains essential information on steganalysis and steganography *New concepts and new applications including QIM introduced *Digital watermark embedding is given a complete update with new processes and applications.
Chapter One: Introduction -- Chapter Two: Applications and Properties -- Chapter Three: Models of Watermarking -- Chapter Four: Message Coding -- Chapter Five: Watermarking with Side Information -- Chapter Six: Structured Dirty-Paper Codes -- Chapter Seven: Analyzing Errors -- Chapter Eight: Using Perceptual Models -- Chapter Nine: Robust Watermarking -- Chapter Ten: Watermark Security -- Chapter Eleven: Content Authentication -- Chapter Twelve: Steganography and Steganalysis.
Includes bibliographical references (p. 549-574) and index.
Keywords: Computer security; Digital watermarking; Data protection; Electronic books